A research project removing heavy metals from wastewater of small-scale gold miners of Camarines Norte (Philippines) using coco-peat as sorbent material - Tanchuling, Maria Antonia N. (ASEAN engineering journal)
The prediction behavior of improved soft soil using vacuum preloading method should be concerned significantly not only in the laboratory but also in the field. It aims at avoiding the risks of instability of the embankment surcharging during construction. The simulation vacuum preloading method using tri-axial apparatus is proposed to predict the behavior of soft soil improvement in the laboratory and the increasing of undrained shear strength of soil specimen at any degree of consolidation...